Water Supply Engineering: Environmental Engineering ( Vol. I) - Santosh Kumar Garg (Delhi, Khanna Publishers, 2022)
In this revised edition, we have provided details of various types of plastic pipers, such as PVC pipes, CPVC pipes, UPVC pipes and DHPE pipes, which now days are being used on a large scale for water supply and sewage plumbing works. Besides, this edition includes the latest Conventional questions of the Engineering Services Exams, as well as of the Civil Services Exams, upto the years 2019 and 2018 respectively, duly supported with Hints and Solutions where required. The author will certainly be grateful if misprints and omissions if any, are brought to his notice, for making amends in the future editions of the book.
Keywords: Water Supply Engineering I Environmental Engineering I Civil Engineering